Shift work and diabetes mellitus: a meta-analysis of observational studies. Issue 1 (16th July 2014) - Gan, Yong; Yang, Chen; Tong, Xinyue; Sun, Huilian; Cong, Yingjie; Yin, Xiaoxu; Li, Liqing; Cao, Shiyi; Dong, Xiaoxin; Gong, Yanhong; Shi, Oumin; Deng, Jian; et al.
Abstract : Background: Observational studies suggest that shift work may be associated with diabetes mellitus (DM). However, the results are inconsistent. No systematic reviews have applied quantitative techniques to compute summary risk estimates. Objectives: To conduct a meta-analysis of observational studies assessing the association between shift work and the risk of DM. Methods: Relevant studies were identified by a search of PubMed, Embase, Web of Science and ProQuest Dissertation and Theses databases to April 2014. We also reviewed reference lists from retrieved articles. We included observational studies that reported OR with 95% CIs for the association between shift work and the risk of DM. Two authors independently extracted data and assessed the study quality. Results: Twelve studies with 28 independent reports involving 226 652 participants and 14 595 patients with DM were included. A pooled adjusted OR for the association between ever exposure to shift work and DM risk was 1.09 (95% CI 1.05 to 1.12; p=0.014; I 2 =40.9%). Subgroup analyses suggested a stronger association between shift work and DM for men (OR=1.37, 95% CI 1.20 to 1.56) than for women (OR=1.09, 95% CI 1.04 to 1.14) (p for interaction=0.01). All shift work schedules with the exception of mixed shifts and evening shifts were associated with a statistically higher risk of DM than normal daytime schedules, and the difference among those shift work schedules was significant (p for interaction=0.04). Conclusions: Shift work is associated with an increased risk of DM. The increase was significantly higher among men and the rotating shift group, which warrants further studies.